Galactosyltransferase 4 is a major control point for glycan branching in N-linked glycosylation - MCDONALD, ANDREW; HAYES, JERRARD; DAVEY, GAVIN; TIPTON, KEITH (My University, 2014)
Protein N-glycosylation is a common post-translational modification that produces a complex array of branched glycan structures. The levels of branching, or antennarity, give rise to differential biological activities for single glycoproteins. However, the precise mechanism controlling the glycan branching and glycosylation network is unknown. Here, we constructed quantitative mathematical models of N-linked glycosylation that predicted novel control points for glycan branching. Galactosyltransferase, which occurs downstream of the glycan branching points, was unexpectedly found to control metabolic flux through the glycosylation pathway and the level of final antennarity of nascent protein produced in the Golgi network. To further investigate the biological consequences for glycan branching of nascent protein we glycoengineered a series of mammalian cells overexpressing human chorionic gonadotropin (HCG). We identified a mechanism in which galactosyltransferase 4 isoform regulated N-glycan branching on the nascent protein, subsequently controlling biological activity in an in vivo model of HCG activity. Galactosyltransferase 4 is a major control point for glycan branching decisions taken in the Golgi of the cell, which may ultimately control the biological activity of nascent glycoprotein.
PUBLISHED
Keywords: Glycosylation; Golgi; branching; Galactosyltransferase; Chorionic gonadotropin; hCG; BIOCHEMISTRY, GLYCOBIOLOGY